Notes on synonymy of Diartiger Sharp with Microdiartiger Sawada (Coleoptera: Staphylinidae: Pselaphinae), with description of two new species from East China - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2013)
The relationship of the clavigerite genera Diartiger Sharp and Microdiartiger Sawada is discussed, and the synonymy of the two genera proposed by Besuchet (1986) is followed. This results in two new combinations: D. thinhi (Nomura), comb. n. and D. songxiaobini (Yin & Li), comb. n. Two new species, D. dentatus Yin & Li, sp. n. and D. yaoluopingensis Yin & Li, sp. n. are described from Anhui, East China, and new locality data for D. songxiaobini from Anhui and Jiangxi is provided. The new species and D. songxiaobini from Anhui were simultaneously collected from colonies of Lasius sp. nesting under stones. The Diartiger species are newly placed in two groups: the D. japonicus-group and the D. fossulatus-group. A key is provided to assist in identification of the Diartiger species from China.